A new species of the bark louse genus Paramanicapsocus (Insecta, Psocodea, Manicapsocidae) from mid-Cretaceous Burmese amber - Chen, Shengfu; Wang, Menglin; Liang, Feiyang (Zootaxa, 2023)
A new fossil psocodean species of the previously monospecific genus Paramanicapsocus is described from Burmese amber, namely Paramanicapsocus xingyuei sp. n.. This new species can be distinguished from the other species P. longiantennatus based on the hindwing vein M two-branched and the female gonapophyses with robust external valves.